LEİSHMANİA TROPİCA'YA KARŞI DNA AŞI ADAYI THİOL SPESİFİC ANTİOXİDANT GENİNİN KLONLANMASI VE GEN DİZİLİMİNİN BELİRLENMESİ - ÖZAVCI, HAMZA (Fırat Üniveristesi, 2019)
Kutanöz Leishmaniasis (KL)' in Türkiye'deki en yaygın etkeni L.tropica' dır. KL'ye karşı en ümit verici aşı adayı moleküllerden biri Thiol Spesific Antioxidant (TSA) proteinidir. Farklı Leishmania türlerine karşı TSA 'nın anlamlı düzeyde koruyucu olduğu saptanmıştır. Bu çalışmada L.tropica Türkiye izolatına ait Thiol Spesific Antioxidant geninin (LtTSA) klonlanması ve gen diziliminin belirlenmesi amaçlandı. L. tropica promastigotlarından izole edilen RNA'dan cDNA sentezlendi. cDNA, TSA genine spesifik primerler kullanılarak PCR ile çoğaltıldı. PCR ürünü ökaryotik hücrelerde çoğalabilen pcDNA3.1 vektörüne klonlandı. Rekombinant plazmid kompetan E. Coli hücrelerine transfekte edilerek çoğaltıldı. PCR tarama, restriksiyon enzim reaksiyonları ve DNA dizi analizi ile klonlama doğrulandı. TSA geninin kodladığı proteinin üç boyutlu yapısı ve antijenik özellikleri belirlendi. LtTSA genine ait 600 baz çiftlik bandlar elektroforezle gösterildi. DNA dizi analizi sonucu LtTSA geninin L. tropica Etiyopya izolatı ve L. aethiopica ile %99; L. donovani, L. infantum, L. chagasi ve L. major ile %97; L. mexicana ile %93 oranında benzer olduğu saptandı. LtTSA geninin kodladığı TSA proteinin ise L. tropica Etiyopya izolatı, L. aethiopica, L. infantum ve L. major TSA proteinlerine sırasıyla %98, %96, %94 ve %93 oranlarında benzediği görüldü. 199 aminoasitlik LtTSA proteininin 7 farklı antijenik bölgesinin olduğu saptandı. TSA proteini farklı Leishmania türlerinde aşı adayı olarak denenmiş ve başarılı sonuçlar elde edilmiştir. Bu çalışmada klonlanan LtTSA ve kodladığı TSA proteininin ise oldukça immünojenik olduğu ve daha önce aşı adayı olarak denenen TSA proteinlerine yüksek oranda benzerlik gösterdiği saptanmıştır. Bu durum TSA proteininin L.tropica Türkiye izolatına karşı muhtemel aşı adayı olabileceğini veya multiantijenik aşıların bir komponenti olarak yer alabileceğini göstermektedir. Anahtar Kelimeler: Leishmania tropica, Thiol Spesific Antioxidant Geni, klonlama, dizi analizi, DNA a?ısı

Cloning and Sequencing of Thiol-Spesific Antioxidant Gene as DNA Vaccine Candidate for Leishmania tropica The most common factor of Cutaneous Leishmaniasis (CL) in Turkey is L. Tropica. One of the most promising vaccine candidate molecules against CL is the Thiol Spesific Antioxidant (TSA) protein. TSA was found to be significantly protective against different Leishmania species. In this study, cloning and determination of gene sequence of Thiol Specific Antioxidant gene (LtTSA) belonging to L. tropica isolate in Turkey were aimed. cDNA was synthesized from the RNA which was isolated from the L. tropica promastigotes. cDNA was amplified by PCR using the specific primers of TSA gene. The PCR product was cloned into the pcDNA3.1 vector, which can replicate in eukaryotic cells. Recombinant plasmid was transfected into competent E. coli cells and amplified. The PCR was confirmed by PCR screening, restriction enzyme reactions and DNA sequence analysis. Three-dimensional structure and antigenic properties of the protein encoded by the TSA gene were determined. 600-base pair bands belonging to the LtTSA gene were shown with electrophoresis. As a result of DNA sequence analysis, the LtTSA gene was found to be 99% similar to the L. tropica Ethiopia isolate and L. aethiopica, 97% similar to L. donovani, L. infantum, L. chagasi and L. major, 93% similar to L. mexicana. TSA protein encoded by the LtTSA gene was found 98%, 96%, 94% and 93% similar to L. tropica Ethiopia isolate, L. aethiopica, L. infantum and L. major TSA proteins respectively. LtTSA protein consisting of 199 amino acids was found to have 7 different antigenic regions. TSA protein was tested as a vaccine candidate in different Leishmania species and successful results were obtained. The cloned LtTSA and encoded TSA protein in this study were found to be highly immunogenic and highly similar to TSA proteins previously tested as a vaccine candidate. This indicates that the TSA protein could be a potential vaccine candidate against the L. tropica Turkey isolate, or a component of multi-antigenic vaccines. Key Words: Leishmania tropica, Thiol Spesific Antioxidant gene, cloning, sequencing, DNA vaccine
Cloning and sequencing of thiol-spesific antioxidant gene as DNA vaccine candidate for leishmania tropica
Keywords: Parazitoloji